2022
DOI: 10.1177/10731911221124340
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Personality Functioning Questionnaire 12-18 (LoPF-Q 12-18): Factor Structure, Validity, and Clinical Cut-Offs

Abstract: The Levels of Personality Functioning Questionnaire 12-18 (LoPF-Q 12-18) is the only self-report measure informed by the Level of Personality Functioning ( Diagnostic and Statistical Manual of Mental Disorders [5th ed.; DSM-5; American Psychiatric Association, 2013]) Alternative Model of Personality Disorders developed for adolescents. The present investigation includes two studies evaluating the English LoPF-Q 12-18. In Study 1, single-factor and bifactor structures (unidimensional severity criterion and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…The LoPF-Q 12-18 scores differentiate adolescents with 5 or more BPD symptoms from the school-based sample of adolescents with BPD (Cohen's d = 1.2), which proved the clinical validity of the LoPF-Q 12-18 (unpublished dataset). Based on the previous discussions about the LoPF-Q structure and existing attempts to identify the most valid structure of the instrument, we have decided to use a total LoPF-Q score as a unidimensional measure of personality functioning [44,45]. In the current study, the internal consistency was excellent for the total scale (α = 0.97).…”
Section: Personality Pathologymentioning
confidence: 84%
“…The LoPF-Q 12-18 scores differentiate adolescents with 5 or more BPD symptoms from the school-based sample of adolescents with BPD (Cohen's d = 1.2), which proved the clinical validity of the LoPF-Q 12-18 (unpublished dataset). Based on the previous discussions about the LoPF-Q structure and existing attempts to identify the most valid structure of the instrument, we have decided to use a total LoPF-Q score as a unidimensional measure of personality functioning [44,45]. In the current study, the internal consistency was excellent for the total scale (α = 0.97).…”
Section: Personality Pathologymentioning
confidence: 84%
“…Likewise, the third ( 16 ) and eleventh ( 36 ) studies reported sensitivity and specificity metrics for two or more PD dysfunction thresholds; on the other hand, study 8 ( 34 ) reported other dysfunction thresholds without these metrics. The fourth ( 15 ) and fifth ( 32 ) studies reported the optimal cut-off points and their diagnostic accuracy metrics according to the setting and reference standard, respectively. Only study 10 ( 38 ) reported additional sensitivity and specificity metrics for all cut-off points of the measure used as an index test.…”
Section: Resultsmentioning
confidence: 99%
“…For the assessment of AMPD Criterion A, a range of self-report and interview-based measures have been developed. These measures show strong validity and reliability in adults [see (15) and ( 16) for a review] and there is an emerging literature validating Criterion A-related measures in adolescents [e.g., (17)(18)(19)(20)]. The limitations of self-report measures to adequately assess Criterion A function, given the known impairment in self-reflection associated with personality pathology, have been noted (21,22), and the potential of using experimental or more performance-based measures has been suggested-in particular for Criterion A (23).…”
Section: Introductionmentioning
confidence: 99%